Kontribusi Kekuatan Otot Lengan terhadap Keterampilan Smash dalam Permainan Bola Voli - Supriyanto Supriyanto; Martiani Martiani (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga, 2019)
This study aims to determine the contribution of arm muscle strength to smash skills in the game of volleyball on extracurricular activities at SMA Negeri 2 Seluma. This study uses the correlation method, which is a correlation analysis technique with product moment statistics, this study uses a sample of 24 students taken by purposive sampling technique. Students have the level of arm muscle strength in the adequate category with an average of 13.46 and the level of smash skills have a level of smash skills in the good category with an average of 18.33, t-count ≥ t-table is 7.62 ≥ 2 .07 at the significance level α = 0.05 (0.5%). Thus it can be concluded that there is a significant relationship between arm muscle strength and smash ability Keywords: Arm Muscle Strength, Smash Skills